align="absmiddle" class="latex-formula">
2 answers:
Answer:
Step-by-step explanation:
(x + y) 2
x2 + 2xy + y2
Answer:
Step-by-step explanation:
This is an example of "the square of a binomial." There is a formula for such cases;
(a + b)^2 = a^2 + 2ab + b^2 (worth memorizing)
Thus, our (x + y)^2 = x^2 + 2xy + y^2
You might be interested in
Answer:
press this link and u will get the answers
https://www.math.tamu.edu/~rosanna/141/WIR2_done.pdf
temperature. ?????? don't understand
Answer:
<h2>This equation has no natural roots.</h2>
Step-by-step explanation:
![3x^2+x-5=0\\\\\text{Use the quadratic formula for}\ ax^2+bx+c=0\\\\x=\dfrac{-b\pm\sqrt{b^2-4ac}}{2a}\\\\\text{For the given equation:}\\\\a=3,\ b=1,\ c=-5\\\\b^2-4ac=1^2-4(3)(-5)=1+60=61\\\\x=\dfrac{-1\pm\sqrt{61}}{(2)(3)}=\dfrac{-1\pm\sqrt{61}}{6}\notin\mathbb{N}](https://tex.z-dn.net/?f=3x%5E2%2Bx-5%3D0%5C%5C%5C%5C%5Ctext%7BUse%20the%20quadratic%20formula%20for%7D%5C%20ax%5E2%2Bbx%2Bc%3D0%5C%5C%5C%5Cx%3D%5Cdfrac%7B-b%5Cpm%5Csqrt%7Bb%5E2-4ac%7D%7D%7B2a%7D%5C%5C%5C%5C%5Ctext%7BFor%20the%20given%20equation%3A%7D%5C%5C%5C%5Ca%3D3%2C%5C%20b%3D1%2C%5C%20c%3D-5%5C%5C%5C%5Cb%5E2-4ac%3D1%5E2-4%283%29%28-5%29%3D1%2B60%3D61%5C%5C%5C%5Cx%3D%5Cdfrac%7B-1%5Cpm%5Csqrt%7B61%7D%7D%7B%282%29%283%29%7D%3D%5Cdfrac%7B-1%5Cpm%5Csqrt%7B61%7D%7D%7B6%7D%5Cnotin%5Cmathbb%7BN%7D)
Answer:
C
Step-by-step explanation:
all other graphs couldnt work because their x axis do not pass the vertical line test.
please give brainliest
Mean = (1+1+2+3+3+3+4+5)/8 = 22/8 = 2.75
answer
mean = 2.75